Non-Litigation Dispute Resolution Mechanism in Civil Law (Case Study at ANQ Law Firm Kudus Office) - Abdullah, Junaidi; -, Shobirin (Program Studi Hukum Keluarga Islam, 2024)
This research focuses on the mechanism of non-litigation dispute resolution in civil law, with a case study at the ANQ Law Firm Kudus Office. A common problem raised is the lack of understanding and application of non-litigation dispute resolution methods, such as mediation, negotiation, and arbitration, which can avoid lengthy and costly court proceedings. The purpose of this study is to analyze the effectiveness of non-litigation dispute resolution mechanisms and the obstacles faced in their implementation. The research method used in this research uses field research with a qualitative approach. How to collect data by observation, documentation and interviews. Meanwhile, data analysis is carried out through data reduction, then displaying data and then verifying the data. The results of the research show that the resolution of non-litigation disputes in civil law at the ANQ law firm office is through visits to the homes of problematic members to deliberate and provide legal education to arouse the awareness of problematic members so that peace is created. This article asserts that while non-litigation mechanisms are effective in most cases, it is important to increase legal awareness and understanding among the public in order to maximize the potential of these methods in civil dispute resolution.